2010
DOI: 10.1152/ajprenal.00374.2009
|View full text |Cite
|
Sign up to set email alerts
|

ANG II receptor blockade enhances anti-inflammatory macrophages in anti-glomerular basement membrane glomerulonephritis

Abstract: ϩ macrophages, with a few CD4 ϩ cells infiltrating the glomeruli. Necrotizing and crescentic glomerular lesions developed by day 7 with the increase of proteinuria. AT 1R was expressed on CD8 ϩ and CD4 ϩ cells and on ED1 ϩ macrophages. Low-dose ARB had no anti-inflammatory effects in anti-GBM GN. However, highdose ARB reduced glomerular infiltration of CD8 ϩ cells and ED1 ϩ macrophages and suppressed necrotizing and crescentic lesions by days 5 to 7 (P Ͻ 0.05). In addition, high-dose ARB reduced the numbers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 50 publications
3
52
0
1
Order By: Relevance
“…The number of synovial macrophages is correlated with the clinical disease activity (34,35); selective macrophage depletion has a strong antiinflammatory effect in animal models of arthritis (36,37). Generally, M1 macrophages are proinflammatory, whereas M2 macrophages are anti-inflammatory (15)(16)(17)(18). We not only showed that E2 potentiated accumulation of macrophages (CD68 + ) among the infiltrated mononuclear cells in the synovium of the inflamed TMJs, but also identified that the accumulated macrophages were mainly M1-like macrophages.…”
Section: Discussionmentioning
confidence: 67%
“…The number of synovial macrophages is correlated with the clinical disease activity (34,35); selective macrophage depletion has a strong antiinflammatory effect in animal models of arthritis (36,37). Generally, M1 macrophages are proinflammatory, whereas M2 macrophages are anti-inflammatory (15)(16)(17)(18). We not only showed that E2 potentiated accumulation of macrophages (CD68 + ) among the infiltrated mononuclear cells in the synovium of the inflamed TMJs, but also identified that the accumulated macrophages were mainly M1-like macrophages.…”
Section: Discussionmentioning
confidence: 67%
“…For example, there is evidence of marked oxidative stress in nephrotoxic serum models of mouse glomerulonephritis, and in particular marked upregulation of NADPH oxidase and increased generation of superoxide free radicals (Kinoshita et al, 2011). Interestingly, these effects were reduced by AT 1 antagonists, which have long been known to reduce histopathologic changes and proteinuria in this model (Suzuki et al, 1998;Mii et al, 2009;Aki et al, 2010). In addition, there is an increase in glomerular intracapillary pressure in these diseases (Maddox et al, 1975;Brenner, 1978), which may lead to increased mechanical stimulation of podocytes (Endlich and Endlich, 2006).…”
Section: Discussionmentioning
confidence: 86%
“…The stimuli for their migration to the kidney and TNF-␣ production are likely increased reactive oxygen species and enhanced expression of endothelial adhesion molecules and chemokines by the kidney in response to elevations in renal-derived TNF-␣. Inhibition of AT 1 receptors (7,121) as well as reactive oxygen scavenging (30) reduces renal-derived TNF-␣, proinflammatory cytokine production, and immune cell infiltration and activation. Similarly, ANG II infusion increases leukocyte infiltration and production of inflammatory cytokines, all of which are prevented by blockade of TNF-␣ with etanercept (33,96).…”
Section: Tumor Necrosis Factor-␣ In the Kidney: Synthesis And Secretionmentioning
confidence: 99%